Single-dose irradiation followed by implant insertion in rat bone. An investigative study to find a critical level for osseointegration - Nyberg, Jan; Hertzman, Sven; Svensson, Börje; Johansson, Petra; Granström, Gösta; Johansson, Carina B. (Journal of Osseointegration, 2010)
Aim No general consensus exists regarding the ideal time to insert implants in bone after irradiation or how the various irradiation doses influence implant success. This study aims at investigating integration of implants in pre-irradiated rat bone and find a critical level doses that cause disturbed osseointegration. Materials and methods Single irradiation doses of 2, 5, 10, 20 and 30 Gy were given to one leg of adult rats 3 days prior to insertion of screw-shaped implants whereas the other leg served as a nonirradiated control. The follow up was 5 weeks. Bone implant contact (BIC) and bone area (BA) were measured on undecalcified cut and ground sections in the light microscope. The tissue quality was also examined in the light microscope. Results Doses of 5 and 10 Gy resulted in 25% higher contact values for the irradiated samples compared to non-irradiated controls. The most impaired integration occurred when doses of 20 Gy were given, revealing a 50% difference between the irradiated (25%) and the non irradiated samples (50%). The bone area demonstrated no major quantitative differences albeit the qualitative observations differed substantially being most pronounced in the 20 and 30 Gy irradiated samples. Conclusions The osseointegration was substantially impaired after radiation doses of 20 and 30 Gy. Quantitative data alone are insufficient to describe implant integration in situation like this. Qualitative observations are of utmost importance and require great attention. The importance of judging and describing various grades of tissue damage is complicated but necessary. Based on the results obtained in this study, full scale experiments are now ongoing.